2022
DOI: 10.1155/2022/7282192
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis of Blood Vessel Stenosis Caused by Arterial Thrombosis of Lower Extremities by Ultrasound Based on the Mobile Information System

Abstract: The thrombosis process is a multifactorial evolution process that includes many genetic and environmental factors that interact with each other. It refers to the existence of blood deposits in the heart or blood vessel walls or abnormal blood clots in the circulatory blood flow during the survival period of humans or animals for some reason. This article aims to analyze the research of blood vessel stenosis caused by arterial thrombosis of the lower extremities under the diagnosis of cardiac ultrasound based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Trombosis of Lower Extremities by Ultrasound Based on the Mobile Information System" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Journal Of Healthcare Engineering Has Retracted the Article ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Trombosis of Lower Extremities by Ultrasound Based on the Mobile Information System" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Journal Of Healthcare Engineering Has Retracted the Article ...mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Diagnosis of Blood Vessel Stenosis Caused by Arterial Thrombosis of Lower Extremities by Ultrasound Based on the Mobile Information System” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%